The addition of mobile SMS effectively improves dengue prevention practices in community: an implementation study in Nepal - Ashmin Hari Bhattarai; Guardian Yoki Sanjaya; Anil Khadka; Randeep Kumar; Riris Andono Ahmad (BMC, 2019)
Abstract Background Dengue is an emerging vector disease with frequent outbreaks in Nepal that pose a major threat to public health. Dengue control activities are mostly outbreak driven, and still lack systematic interventions while most people have poor health-related knowledge and practices. Mobile Short Message Service (SMS) represents a low-cost health promotion intervention that can enhance the dengue prevention knowledge and practices of the affected communities. This study aimed to explore the acceptability, appropriateness, and effectiveness of mobile SMS intervention in improving dengue control practices. Methods This study was an implementation research that used mixed-methods design with intervention. A total of 300 households were divided into three groups, i.e. one control group, one dengue prevention leaflet (DPL) only intervention group and one DPL with mobile SMS intervention group (DPL + SMS). We used a structured questionnaire to collect information regarding participants' knowledge and practice of dengue prevention. We conducted in-depth interviews with key informants to measure acceptability and appropriateness of intervention. Mean difference with standard deviation (SD), one-way ANOVA, paired t-test and regression analyses were used to assess the effectiveness of the interventions. Thematic analysis was used to assess the acceptability, and appropriateness as well as barriers and enablers of the intervention. Results The DPL + SMS intervention produced significantly higher mean knowledge difference (32.7 ± 13.7 SD vs. 13.3 ± 8.8 SD) and mean practice difference (27.9 ± 11.4 SD vs 4.9 ± 5.4 SD) compared to the DPL only group (p = 0.000). Multivariate analysis showed that the DPL + SMS intervention was effective to increase knowledge by 28.6 points and practice by 28.1 points compared to the control group. The intervention was perceived as acceptable and appropriate by the study participants and key stakeholders. Perceived barriers included reaching private network users and poor network in geographically remote areas, while enabling factors included mobile phone penetration, low cost, and shared responsibility. Conclusions Mobile SMS is an effective, acceptable and appropriate health intervention to improve dengue prevention practices in communities. This intervention can be adopted as a promising tool for health education against dengue and other diseases.